2019
DOI: 10.3390/brainsci9060145
|View full text |Cite
|
Sign up to set email alerts
|

The Counteracting Effects of Exercise on High-Fat Diet-Induced Memory Impairment: A Systematic Review

Abstract: The objective of the present review was to evaluate whether exercise can counteract a potential high-fat diet-induced memory impairment effect. The evaluated databases included: Google Scholar, Sports Discus, Embase/PubMed, Web of Science, and PsychInfo. Studies were included if: (1) an experimental/intervention study was conducted, (2) the experiment/intervention included both a high-fat diet and exercise group, and evaluated whether exercise could counteract the negative effects of a high-fat diet on memory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…This research follows the instructions of the preferred reporting items for systematic review and meta-analysis (PRISMA) statement [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…This research follows the instructions of the preferred reporting items for systematic review and meta-analysis (PRISMA) statement [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…A sedentary lifestyle and physical inactivity (insufficient exercises time) are prevalent among children and adolescents (Sisson et al, 2009 ; Qi et al, 2019 ) and are negatively linked with their physical and psycho-cognitive health (Tremblay et al, 2011 ; Flashner et al, 2019 ). Specifically, these unhealthy lifestyle behaviors result in obesity (Rey-Lopez, 2008 ), uncoordinated movements (Ferguson et al, 2014 ; Flashner et al, 2019 ; Kong et al, 2019 ; Riquelme et al, 2019 ), negative emotions (depression, anxiety, suicide attempts) (Berardelli et al, 2018 ; Thivel et al, 2018 ; Padulo et al, 2019 ) and a severe deficit of cognitive functions (Torrens-Burton et al, 2017 ; Koolhaas et al, 2019 ; Loprinzi et al, 2019 ). Among the components of cognitive functioning, inhibitory control, working memory, and cognitive flexibility play a critical role in the development of school-age children and their educational achievement or academic performance (Best, 2010 ; Willoughby et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the cognitive flexibility component of executive function is an important prerequisite for reversal learning [14] and acute exercise has been shown to subserve cognitive flexibility [15][16][17]. Further, chronic high-fat diet consumption has been shown to impair reversal learning and reduce BDNF levels [18], yet we have shown that exercise can counteract these effects [19]. Collectively, there is theoretical support for a relationship between acute exercise and reversal learning.…”
Section: Introductionmentioning
confidence: 73%